Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
-23.63+23.21-58.23
=23(-63+21-58)
=23.(-100)
=-23000
-23.63+23.21-58.23
=23.(-63)+23.21-58.23
=23.(21-63-58)
=23.(-100)
=-2300
\(a.\left(-83\right)+302+83\\ =\left(-83+83\right)+302\\ =0+302\\ =302\\ b.14.\left(-7\right)-216:2\\ =-98-108\\ =-206\\ c.56.\left(-32\right)+\left(-68\right).56\\ =56.\left[\left(-32\right)+\left(-68\right)\right]\\ =57.\left(-100\right)\\ =-5700\\ d.2^3-6.\left[25-\left(33-28\right)^2\right]\\ =8-6\left[25-5^2\right]\\ =8-6\left[25-25\right]\\ =8-6.0\\ =8-0\\ =8\\ e.15.\left(-6\right)-420:\left(-4\right)\\ =-90-\left(-105\right)\\ =-90+105\\ =15\)
\(f.63.\left(-52\right)+\left(-48\right).63\\ =63.\left[\left(-52\right)+\left(-48\right)\right]\\ =63.\left(-100\right)\\ =-6300\)
a: \(-81\cdot36+\left(-81\right)\cdot63-81\)
\(=36\cdot\left(-81\right)+63\cdot\left(-81\right)+\left(-81\right)\)
\(=-81\left(36+63+1\right)\)
\(=-81\cdot100=-8100\)
b: \(23\cdot\left(-38+123\right)-123\cdot\left(23-38\right)\)
\(=-23\cdot38+23\cdot123-123\cdot23+123\cdot38\)
\(=123\cdot38-23\cdot38=38\left(123-23\right)=38\cdot100=3800\)
-23 x 63 + 23 x 21 - 58 x 23
= 23 x ( -63 + 21 - 58 )
= 23 x ( -100 )
= -2300
\(-23\cdot63+23\cdot21-58\cdot23\)
\(=23\left(-63+21-58\right)\)
\(=23\cdot\left(-100\right)\)
\(=-2300\)
a) 1125 - (374 + 1125) + (-65 + 374)
= 1125 - 374 - 1125 + (-65) + 374
= (1125 - 1125) + (-374 + 374) + (-65)
= 0 + 0 + (-65)
= -65
b) -23. 63 + 23 . 21 - 58 . 23
= 23 .(-63) + 23 . 21 - 58 . 23
= 23 . [(-63) + 21 - 58]
= 23 . (-100)
= -2300
c) -2003 + (-21 + 75 + 2003)
= -2003 + (-21) + 75 + 2003
= (-2003 + 2003) + (-21) + 75
= 0 + 54
= 54
d) 942 - 2567 + 2563 - 1942
= (942 - 1942) + (-2567 + 2563)
= -1000 + (-4)
= -1004
e) 12 - 12 + 11 + 10 - 9 + 8 - 7 + 5 - 4 + 3 + 2 - 1
= 0 + 11 + 1 + 1 + 1 + 3 + 1
= 18
1a) -54 . 76 + 12 .(-76) + 76.(-34)
= (-54 - 12 - 34).76
= -100 . 76
= -176
b) 37.(63 - 24) - 63.(24 + 37)
= 37 . 63 - 37 . 24 - 63.24 - 63 . 37
= (37.63 - 63.37) - (37 + 63) . 24
= 0 - 100 . 24
= - 2400
2a) x + (-27) = -23 - x
=> x + x = -23 + 27
=> 2x = 4
=> x = 4 : 2
=> x = 2
b) xy + 2x - y = 15
=> x(y + 2) - y = 15
=> x(y + 2) - (y + 2) = 13
=> (x - 1)(y + 2) = 13 = 1 . 13 = 13 . 1
Lập bảng :
x - 1 | 1 | -1 | 13 | -13 |
y + 2 | 13 | -13 | 1 | -1 |
x | 2 | 0 | 14 | -12 |
y | 11 | -15 | -1 | -3 |
Vậy ...
\(\left(9^{98}\cdot80+9^{98}\right):9^{100}\)
\(=\frac{9^{98}\cdot80+9^{98}}{9^{100}}\)
\(=\frac{9^{98}\cdot\left(80+1\right)}{9^{100}}\)
\(=\frac{9^{98}\cdot81}{100}\)
\(=\frac{9^{98}\cdot9^2}{9^{100}}\)
\(=\frac{9^{100}}{9^{100}}=1\)
=[(-216):(-9)]+[180:(-9)]-[63:(-9)]
=24+(-20)-(-7)
=4-(-7)
=11
đúng thì tick cho nha!